Mexico’s Telesecundaria Program and Equitable Access to Resources - Craig, Dana; Etcheverry, Jose; Ferris, Stefan (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2016)
This Note provides an analysis of Mexico’s Telesecundaria program within the context of Mexico’s new education reform framework offering a succinct background of the project, as well as key policy lessons that can be useful for other jurisdictions interested in the development of distance education programs. This Note uses a literature and data analysis review approach, as well as qualitative analysis of interview data collected recently in Mexico by the authors. The Note positions pedagogical approaches to distance education within the context of developments in communication, internet access and renewable energy technologies, as well as within the challenges of the digital divide as means of powering digital access to information and education to remote, rural and marginalized communities.